Insights into CANDLE Syndrome - Katarina Kieselová; Felicidade Santiago; Martinha Henrique (Sociedade Portuguesa de Dermatologia e Venereologia, 2020)
Chronic atypical neutrophilic dermatosis with lipodystrophy and elevated temperature (CANDLE) syndrome is a recently described chronic autoinflammatory disease, pathophysiologically related to intracellular proteasome/immunoproteasome dysfunction. This review chronicles the recognition of CANDLE syndrome, the developments in the understanding of the pathomechanism, genetic background, and the emerging therapeutic strategies of this condition.